Mechanistic Approach for Toxic Effects of Bupropion in Primary Rat Hepatocytes - Ahmadian, Elham; Babaei, Hossein; Mohajjel Nayebi, Alireza; Eftekhari, Aziz; Eghbal, Mohammad Ali (Drug Research, 2017)
Bupropion is a widely prescribed antidepressant/smoke cessation drug. However, hepatotoxicity is one of its side effects reported in some recipients. The mechanisms by which bupropion induces hepatotoxicity is not clear yet. This experiment was intended to assess the cytotoxic mechanisms of bupropion toward primary rat hepatocytes. Additionally, the effect of α-tocopherol succinate (ALPHA-TOS) and N-acetyl cysteine (NAC) and mitochondrial permeability transition (MPT) pore sealing agent cyclosporine A (Cs A) on this toxicity was investigated. Cell death, LDH leakage, reactive oxygen species (ROS) generation, lipid peroxidation (LPO), and mitochondrial depolarization were examined as toxicity indicators. Results revealed that bupropion led to a surge in ROS formation, depletion of intracellular glutathione, elevation of LPO, and mitochondrial collapse. ALPHA-TOS, NAC and Cs A administration diminished the intensity of cellular damage caused by bupropion. This experiment suggests the protective role of ALPHA-TOS, NAC and Cs A against bupropion-mediated cytotoxicity possibly through their reactive radical scavenging properties and their impacts on mitochondria. Furthermore, mitochondria might be contributed to the oxidative stress response and subsequent toxicological results observed by bupropion.
Keywords: bupropion; oxidative stress; antioxidant; mitochondria; cytotoxicity